2009
DOI: 10.1194/jlr.m800655-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Infection decreases fatty acid oxidation and nuclear hormone receptors in the diaphragm

Abstract: there is increasing evidence that decreased ventilatory muscle contraction contributes signifi cantly to this respiratory failure ( 3,4 ). Friman ( 5 ) reported that in humans, the maximal force that a muscle can produce and the endurance capacity of muscle decreases during infections. Moreover, animal models of infection also showed a decrease in the force that the ventilatory muscles can generate, leading to hypercapneic respiratory failure ( 3,4,6 ). Additionally, endotoxin (lipopolysaccharide, LPS) adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
2
34
3
Order By: Relevance
“…An early study found that LPS, TNF, and IL-1 augment PGC-1 expression resulting in increased oxidative phosphorylation while more recently, sepsis was shown to lower PGC-1 and PGC-1 in skeletal muscle of rats [61,285]. In support of these data, PGC-1 and PGC-1 are also reduced in diaphragm after LPS administration with concomitant decrease in fatty acid oxidation [286]. A more careful examination of the time-course revealed that intraperitoneal injection of LPS induced PGC-1 in skeletal muscle after 2h, but decreased its expression after 24h, suggesting a shortterm up-but a long-term down-regulation [287].…”
Section: Mutual Influence Of Inflammatory Factors and Pgc-1smentioning
confidence: 88%
“…An early study found that LPS, TNF, and IL-1 augment PGC-1 expression resulting in increased oxidative phosphorylation while more recently, sepsis was shown to lower PGC-1 and PGC-1 in skeletal muscle of rats [61,285]. In support of these data, PGC-1 and PGC-1 are also reduced in diaphragm after LPS administration with concomitant decrease in fatty acid oxidation [286]. A more careful examination of the time-course revealed that intraperitoneal injection of LPS induced PGC-1 in skeletal muscle after 2h, but decreased its expression after 24h, suggesting a shortterm up-but a long-term down-regulation [287].…”
Section: Mutual Influence Of Inflammatory Factors and Pgc-1smentioning
confidence: 88%
“…Because it has been shown that this effect occurs within 2 h after LPS administration and is sustained for at least 24 h ( 29, 30 ), medium-chain acylcarnitines and phospholipids might be appropriate biomarkers for differentiation of sepsis and noninfectious SIRS in the early stage of the disease. the result of a coordinated, predominantly down-regulation of many proteins taking part in FA transport , FA oxidation (carnitine palmitoyl transferase, medium chain acyl CoA dehydrogenase [MCAD]), and the breakdown of triglycerides (LPL) (17)(18)(19)(20). A well characterized enzyme taking part in FA oxidation that is suppressed in sepsis is MCAD ( 17,19 ).…”
Section: Discussionmentioning
confidence: 99%
“…the result of a coordinated, predominantly down-regulation of many proteins taking part in FA transport , FA oxidation (carnitine palmitoyl transferase, medium chain acyl CoA dehydrogenase [MCAD]), and the breakdown of triglycerides (LPL) (17)(18)(19)(20). A well characterized enzyme taking part in FA oxidation that is suppressed in sepsis is MCAD ( 17,19 ). This mitochondrial enzyme processes FAs bound to CoA (acyl-CoA) with a chain length of C5-C14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in VLDL during sepsis, traditionally considered as a reaction mobilizing lipid stores to delivery an increased amount to the immune cells, may also have a protective meaning: the increased level of serum VLDL and of their content in phospholipids can substitute for the HDL in binding and neutralizing LPS [119,120].…”
Section: Vldlmentioning
confidence: 99%